A spatial approach to the study of competition between toolstones in specific regional contexts - Barrientos, Gustavo (2017)
Fil: Barrientos, Gustavo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Antropología; Argentina